Application of affine theorem to orthotropic rectangular reinforced concrete slab with unequal corner opening - Rambabu, K.; Goli, H. B.; YajDani, Shaik. (Journal of Structural Engineering, 2025)
An attempt has been made to apply affinity theorem to two-way orthotropic slab with corner opening whose aspect ratio is different to that of the given slab. Keeping in view the basic principles of yield line theory, all possible admissible yield line patterns are considered for the given configuration of the slab subjected to uniformly distributed load. A computer program has been developed to solve the virtual work equations for the admissible yield line failure patterns of the slab for given different data. Illustration of above methodology has been brought out with numerical examples. Some relevant tables, two charts for given data and the governing admissible failure patterns of the slab are presented using the affine theorem.